Pension as a measure of social protection to reduce inequality. Rethinking the peruvian system - Carranza Acevedo, Renata (2020)
In order to fulfill their obligations to guarantee fundamental rights and reduce inequalities States have a series of options; one of them, the implementation of policies aimed at improving the standard of living of their population; that is how the concept of social security gains relevance, but not as a social policy under the charity paradigm but as a state management strategy, under the comprehension that social security is a fundamental right. In that sense, the present article aims to denote that social security regarding pensions has a significant impact on reducing inequality and as a consequence it is necessary to apprehend it as a public protection policy centered on the person for the realization of their rights, with the management and control of the State from the implementation of redistributive measures such as the universalization of non-contributory pensions but hand in hand with policies that aim to reverse the causes of structural inequality that generate the lack of coverage and adequacy around access to pensions for the elderly, on which we will focus, as they are a group in a disadvantaged situation. Therefore, firstly, we will delineate the relationship between pensions as measure of social security and inequality, secondly, we will provide an overview of how the pension system for the elderly is constituted in Peru; finally, we will analyze the current panorama of coverage and sufficiency that result in the (in)satisfaction of the right to social security and in which women are especially relegated, since state interventions have to start from a diagnosis that identifies the main challenges that the pension system will have to deal with.